Interfacial charge transfer weakens hydrogen bonds between water molecules to accelerate solar water evaporation. Issue 14 (22nd March 2023) - Wang, Liru; Lin, Jinguo; Li, Yuanyuan; Yang, Yanan; Liu, Xiaoting; Wang, Zhe; Liu, Feng; Sun, Xiaotong; Yang, Tian; Chen, Nan; Qu, Liangti
Abstract : A highly polar surface photothermal material is designed to weaken the strength of the hydrogen bond between the intermediate water (IW) and the bound water (BW) to improve the water evaporation rate of the interface solar absorber. Abstract : The evaporation of water requires considerable energy as it must break the hydrogen bonds that account for 5/6 of the total intermolecular forces of water in addition to breaking the intermolecular forces. The same is true for solar interfacial water evaporation to produce pure water. The problem of how to weaken the hydrogen bonds between liquid water molecules in a solar absorber below the boiling point of water to increase the evaporation rate has not been focused upon. We designed a reduced graphene oxide (rGO)-based foam (rGOFpl foam) with a surface rich in highly polar units as a solar absorber. Theoretical simulations confirm that the charge transfer at the solid–liquid interface brought by highly polar units such as MgF2 affects the charge distribution of adjacent water molecules, forming more interstitial water layers with weak intermolecular hydrogen bonds and easy evaporation. rGOFpl foam has a water vapor production rate of 1.83 kg m −2 h −1 under 1 kW m −2 solar radiation, which is 1.87 times higher than that of the rGO foam and much higher than some previously reported ones for certain conventional rGO-based solar absorbers. This study provides an important theoretical basis for the design of future solar thermal absorbers and paves the way for the practical application of cost-effective solar interfacial water evaporation technology.